Semi-automatic Assembly of 3D Virtual Scenarios Over Parametric Models: A Study of Electrical Power Substations - Ferreira, Angel R.; Silva, Alexandre C.; de Lima, Diogo Aparecido Cavalcante; Aureliano Júnior, Maurício J.; Cardoso, Alexandre; Lamounier Junior, Edgard (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Considering the increasing demand for three-dimensional (3D) virtual models in the business of industry and the implication of concepts that are already widely accepted, the investigation was conducted on the methods for obtaining virtual models of the industrial environment, with the case study being conducted in the electric sector. A 3D authoring tool based on parametric models and a data-oriented file structure (conventional in JSON Schema) were developed for the assembly of 3D virtual environment scenarios. In order to demonstrate the usefulness of the developed architectures, we tested their application in the assembly of conceptual scenes of electrical substation arrangements.